Pengaruh Kompensasi Eksekutif, Beban Pajak Tangguhan dan Faktor Lainnya Terhadap Penghindaran Pajak - Hanuna Zahra Ghassani; Retno Indah Hernawati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to collect direct evidence that shows how tax avoidance is influenced by leverage, profitability, firm size, capital strength, audit committee, executive compensation, and deferred tax expense. The research population from the Non-Cylical Consumer category in the food and beverages sub-sector listed on the Indonesia Stock Exchange (IDX) uses 44 companies with a total of 120 samples selected through purposive sampling method, for three years (2021-2023). The method used in this research is panel data regression analysis with Eviews 12 analysis tool. The results showed that company size and audit committee affect tax avoidance while profitability, leverage, capital intensity, executive compensation, and deferred tax expense have no effect on tax avoidance. Company size affects tax avoidance through the ability to optimize complex transaction structures and accessibility to tax expertise, while the audit committee is influential because of its involvement in fiscal strategies that sometimes prioritize tax efficiency over its normative oversight function.